On the effectiveness of incorporating shear thickening fluid with fumed silica particles in hip protectors. (18th December 2017) - Haris, A; Goh, B W Y; Tay, T E; Lee, H P; Rammohan, A V; Tan, V B C
Abstract: The objective of this research is to develop a smart hip protector by incorporating shear thickening fluid (STF) into conventional foam hip protectors. The shear thickening properties of fumed silica particles dispersed in liquid polyethylene glycol (PEG) were determined from rheological tests. Dynamic drop tests, using a 4 kg drop platen at 0.5 m drop height, were conducted to study how STF improves energy absorption as compared to unfilled foam and PEG filled foam. The results show that PEG filled foam reduces the mean peak force transmitted by a further 55% and mean peak displacement by 32.5% as compared to the unfilled foam; the STF filled foam further reduces mean peak force and displacement by 15% and 41% respectively when compared to the PEG filled foam. At a displacement of 22 mm, the STF filled foam absorbs 7.4 times more energy than the PEG filled foam. The results of varying the drop mass and drop height show that the energy absorbed per unit displacement for STF filled foam is always higher than that of PEG filled foam. Finally, the effectiveness of a prototype of hip protector made from 15 mm thick STF filled foam in preventing hip fractures was studied under two different loading conditions: distributed load (plate drop test) and concentrated load (ball drop test). The results of the plate and ball drop tests show that among all hip protectors tested in this study, only the prototype can reduce the mean peak impact force to be lower than the force required to fracture a hip bone (3.1 kN) regardless of the type of loading. Moreover, the peak force of the prototype is about half of this value, suggesting thinner prototype could have been used instead. These findings show that STF is effective in improving the performance of hip protectors.